2022
DOI: 10.1038/s41396-022-01258-z
|View full text |Cite
|
Sign up to set email alerts
|

Globally distributed mining-impacted environments are underexplored hotspots of multidrug resistance genes

Abstract: Mining is among the human activities with widest environmental impacts, and mining-impacted environments are characterized by high levels of metals that can co-select for antibiotic resistance genes (ARGs) in microorganisms. However, ARGs in mining-impacted environments are still poorly understood. Here, we conducted a comprehensive study of ARGs in such environments worldwide, taking advantage of 272 metagenomes generated from a global-scale data collection and two national sampling efforts in China. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 92 publications
(122 reference statements)
2
17
0
Order By: Relevance
“…The e ux of these compounds is closely related to interfacial colonization and nutrient acquisition of soil bacteria and are themselves a compensatory mechanism for the cost of resistance expression. Furthermore, consistent with our observation, previous studies also reported the prevalence of MDR genes in natural and anthropogenically affected soil (Qian et al 2021, Thomas IV et al 2020, Yi et al 2022). In the study of the Savannah River Site (Thomas IV et al 2020), high abundances of multidrug resistance genes were found in all 24 acidic (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The e ux of these compounds is closely related to interfacial colonization and nutrient acquisition of soil bacteria and are themselves a compensatory mechanism for the cost of resistance expression. Furthermore, consistent with our observation, previous studies also reported the prevalence of MDR genes in natural and anthropogenically affected soil (Qian et al 2021, Thomas IV et al 2020, Yi et al 2022). In the study of the Savannah River Site (Thomas IV et al 2020), high abundances of multidrug resistance genes were found in all 24 acidic (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In recent studies through the metagenomic analysis with structured databases and newly developed bioinformatics tools, new insights into the environmental resistome were uncovered (Alcock et al 2019, Boolchandani et al 2019, Yin et al 2018, among which the high prevalence of multidrug resistance (MDR) genes in the soil has raised concerns (Qian et al 2021, Thomas IV et al 2020, Yi et al 2022. The vast majority of MDR genes are associated with e ux pumps, which are integral membrane transport proteins that function to extrude antibiotics from bacterial cells (Henderson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, consistent with our observation, previous studies also reported the prevalence of MDR genes in natural and anthropogenically affected soil. 25,26,28 In a study of the Savannah River Site, 26 high abundances of multidrug resistance genes were found in all 24 acidic (i.e., pH 3.98−4.38) and heavy metal polluted soils. If in this situation it can still be explained by heavy metal coselection at contaminated sites, the prevalence of multidrug resistance genes in 26 rainforest and pasture soil samples could only be attributed to the natural selection of soil properties.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In recent studies through the metagenomic analysis with structured databases and advanced bioinformatics tools, new insights into the environmental resistome were uncovered, among which the high prevalence of multidrug resistance (MDR) genes in the soil raised concerns. The vast majority of MDR genes are associated with efflux pumps, which are integral membrane transport proteins that function to extrude antibiotics from bacterial cells . The “multidrug” was named as, typically, they did not recognize only one class of antibiotics but a wide range of chemically dissimilar compounds, and thus, a single efflux pump may provide resistance to a wide range of antibiotics. , For instance, the tripartite AcrAB-TolC complex confers clinically significant resistance to more than six categories of antibiotics including β-lactams, quinolones, macrolides, and tetracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…It has become evident, in the last decade, that environments such as surface water systems harbor metal-resistant and antibiotic-resistant bacteria (Squadrone 2020;Truong et al 2021). More so, the presence of metal-resistant and antibiotic-resistant bacteria in water has raised significant concerns (Squadrone 2020;Anand et al 2021), while recent studies have started to identify multiple resistant genes associated with heavy metal impacted environments (Rajasekar et al 2022;Yi et al 2022). Nonetheless, information on the impacts of the physico-chemical properties of water on the metal and antibiotic resistance of bacteria is still lacking in South Africa.…”
Section: Introductionmentioning
confidence: 99%